A Psychoanalytic Approach to Turkish Foreign Policy: Crisis, Disorder, and Disorientation - Adisonmez, Umut Can; Oztig, Lacin Idil (TAYLOR & FRANCIS LTD, 2025)
What explains Turkey's current foreign policy disorientation, causing the country to swing from one position to another in a relatively short period of time? We argue that rational arguments do not provide comprehensive explanations of the fluctuations in Turkish foreign policy. By utilising a psychoanalytic approach, this study argues that the relentless radical developments that unfolded at home and abroad in the past decade paralysed the Turkish leadership, disrupting their sense of order in international politics while detaching them from important geopolitical realities. Under this neurotic condition, Turkey's leadership has engaged in a constant seek for recognition as a key regional player irrespective of how controversial these efforts may be. In making sense of this case, this study builds on the ontological security literature in International Relations and contributes to the existing debates on foreign policy crises by integrating a Lacanian notion of jouissance to the ontological security framework. It shows that the jouissance approach offers a productive lens which captures how an ontologically insecure state like Turkey follows disorderly conducts in international politics and gains satisfaction from it as a way to reassure its ruptured sense of actorness at times of multiple crises.
Keywords: Turkey; crisis; disorientation; foreign policy; jouissance; ONTOLOGICAL SECURITY; WORLD-POLITICS; IDENTITY; ANXIETY; NATIONALISM; COOPERATION; CONFLICT; POPULISM; VALUES; International Relations; Government & Law